IMPLEMENTASI PENDIDIKAN KARAKTER JUJUR DAN BERTANGGUNG JAWAB PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA TAHFIDZ AL-QUR'AN DAN SAINS (SMP TQS) ASSALAAM TEPUS GUNUNGKIDUL YOGYAKARTA TAHUN AJARAN 2023/2024 - Ahmad Sholihin; Mu'in Abdullah; Yuni Safitri (STKIP Pesisir Selatan, 2026)
Objective: This study aims to examine the implementation of honesty and responsibility character education and to identify its supporting and inhibiting factors at SMP TQS Assalaam Tepus, Gunungkidul, Yogyakarta, in the 2023/2024 academic year. Methods: The study employed a qualitative method with a descriptive case study approach. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with source and technique triangulation used to ensure data validity. Results: The findings indicate that character education was implemented through habituation of completing tasks independently, monitoring of worship and Qur’anic memorization emphasizing honesty, supervision by teachers and dormitory supervisors, teacher role modeling, persuasive approaches, and a religious school culture. Supporting factors include the boarding school environment, an integrated curriculum, and the role of educators, whereas inhibiting factors arise from family background, peer influence, and gadget use. Novelty: The implementation positively affected students’ honesty in reporting activities, academic and religious responsibility, discipline, and self-awareness. The program also improved students’ discipline and social awareness.